(1)
(f+g)(x) = 6x^2+2x-7+4x-3=6x^2+6x-10
(f-g)(x)=6x^2+2x-7-4x+3 = 6x^2-2x-4
(2)
(f+g)(x)=2x-3x+1-2x=-3x+1
(f-g)(x)=2x-3x-1+2x=x-1
Answer:7881 years
Step-by-step explanation:
You can use the equation
fraction remaining = 0.5n where n is # of half lives elapsed
n = ?
fraction remaining = 1 - 0.612 = 0.388
0.388 = 0.5n
n = 1.37 = the # of half lives
1.37 x 5750 yrs = 7881 years
5/12-2/5=25/60-24/60
1/60
the answer is 1/60
Answer:
80,10,66
Step-by-step explanation:
Hope this helps :)
Hi there!
First you simplify.
Simplified = 9x+(−5)+(−8)+x
Then you combine the like terms.
<span><span><span><span><span>9x</span>+(<span>−5)</span></span>+(<span>−8)</span></span>+x (*-5 and -8 are like terms) (9x and x are like terms)
</span></span><span><span><span>Combined it's~ (<span><span>9x</span>+x</span>)</span>+<span>(<span><span>−5</span>+<span>−8</span></span>)
</span></span></span><span><span><span>Solve and that comes to 10x</span>+<span>−<span>13 which is your answer. :)
Hope this helps.
</span></span></span></span>